The Charlemont Library, the Sotheby Warehouse Fire of 1865, and the Vexed Provenance of British Library MS Egerton 1994. (10th March 2022) - Freeman, Arthur; Freeman, Janet Ing
Abstract: This article discusses the book collection of James Caulfeild (1728–1799), first earl of Charlemont in the Irish peerage, with particular reference to his holdings of early English drama and poetry. After the death of Charlemont's son the library was consigned to Sotheby's for anonymous sale in July 1865, but was in large part destroyed in the Sotheby warehouse fire of 19 June. The second part of the article explores the provenance of one surviving item, a volume of fifteen manuscript plays composed over four or five decades before 1644, now British Library, MS Egerton 1994. It is among the most interesting survivals known from the slender corpus of pre-Restoration English stage documents. Charlemont's principal London agent for early English books, the Shakespeare editor Edmond Malone (1741–1812), has long been viewed as the source of the volume. The history of this speculation is traced and disproved.